Liquid state bioconversion of domestic wastewater sludge for bioethanol production - Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Razak, A A (2007)
The production of bioethanol was conduct-ed by utilizing domestic wastewater sludge as major substrate using the yeast, Saccharomyces cerevisiae in liquid state bioconversion method (submerged fermenta-tion). The optimum media and process conditions ob-tained from previous studies by using central composite design were applied in this study to evaluate the biocon-version process through ethanol production. The results presented in this study showed that 9.8% ethanol was produced utilizing sludge as substrate by Saccharomyces cerevisiae within 48 hours of fermentation while the COD, copper and chromium (heavy metals) removal were found to be 62%, 68% and 45% respectively in treated sludge after 72 hours of fermentation period. The total suspended solids (TSS) as biosolids (microbial growth) was observed to evaluate the microbial perfor-mance in bioconversion process. The observed yield and productivity were determined as well.